2021
DOI: 10.1155/2021/6034147
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Network Pharmacology and Experimental Validation Deciphers the Mechanism of Guizhi Fuling Wan against Adenomyosis

Abstract: Aim. This study aimed to predict the key targets and endocrine mechanisms of Guizhi Fuling Wan (GZFLW) in treating adenomyosis (AM) through network pharmacology, molecular docking, and animal experiment verification. Methods. The related ingredients and targets of GZFLW in treating AM were screened out using TCMSP, BATMAN-TCM, SwissTargetPrediction, and PubChem Database. Then, the protein-protein interaction (PPI) analysis and the network of compound-hub targets were constructed. At the same time, the key targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Codonopsis pilosula (20 g) was added to the prescription when patients presented with significant "qi" deficiency syndrome. In previous research, ingredients and targets of these herbs were downloaded from the traditional Chinese medicine systems pharmacology database [14][15][16][17]. An ingredient was defined as active when a combination of the following conditions was true: OB > 30% and DL > 0:18.…”
Section: Drug Formulationsmentioning
confidence: 99%
“…Codonopsis pilosula (20 g) was added to the prescription when patients presented with significant "qi" deficiency syndrome. In previous research, ingredients and targets of these herbs were downloaded from the traditional Chinese medicine systems pharmacology database [14][15][16][17]. An ingredient was defined as active when a combination of the following conditions was true: OB > 30% and DL > 0:18.…”
Section: Drug Formulationsmentioning
confidence: 99%
“…Modern pharmacological studies showed that GFW could reduce the expression of vascular endothelial growth factor (VEGF), interleukin-2 (IL-2), and interleukin-8 (IL-8) in serum [ 11 ] and was found to be effective in rat models of AM [ 12 , 13 ]. Wang verified that GFW played a role in treating AM by regulating the estrogen signaling pathway [ 14 ]. Our group also performed some research on GFW in treating AM.…”
Section: Introductionmentioning
confidence: 99%